2014
DOI: 10.1007/s11664-014-3090-9
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Telluride Solar Cells on Ultrathin Glass for Space Applications

Abstract: This paper details the preliminary findings of a study to achieve a durable thin film CdTe photovoltaic device structure onto ultra-thin space qualified cover glass. An aluminium doped zinc oxide (AZO) transparent conducting oxide (TCO) was deposited directly onto cover glass

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…After the light intensity correction, we found that 96.8% of original PCE of the perovskite solar cell device retained after the long‐term radiation stability test. It is noted that light loss can be alleviated by using different types of glass, for example, the cerium doped glass, which can avoid the formation of color centers under radiation in space. Self‐healing behavior of the perovskite device was observed upon irradiation.…”
Section: Photovoltaic Parameters Of a Perovskite Device Before And Afmentioning
confidence: 99%
“…After the light intensity correction, we found that 96.8% of original PCE of the perovskite solar cell device retained after the long‐term radiation stability test. It is noted that light loss can be alleviated by using different types of glass, for example, the cerium doped glass, which can avoid the formation of color centers under radiation in space. Self‐healing behavior of the perovskite device was observed upon irradiation.…”
Section: Photovoltaic Parameters Of a Perovskite Device Before And Afmentioning
confidence: 99%
“…Sample A was deposited on a 50 µm cover glass and sample B a 100 µm cover glass. The results of both of these samples have both been reported elsewhere, but are reiterated here to demonstrate the progress made [13, 14]. Samples C and D were deposited onto a chemically toughened 100 µm cover glass which is now the substrate of choice for further development of this device structure.…”
Section: Methodsmentioning
confidence: 59%
“…The R s was significantly reduced from 11.2 to 3.3 Ω·cm 2 between samples A and D. The most significant decrease in R s was observed between samples A and B, both of which did not benefit from the high‐resistivity ZnO layer or indeed the post‐growth anneal in the air. For this decrease in R s no change was made to the back contacting, and was attributed to an improvement of the front contact resistance in a previous publication [14]. The authors described how sample A had one front contact made to the AZO along one side of the 60 × 60 mm substrate using a gold wire embedded in a silver paint.…”
Section: Resultsmentioning
confidence: 96%
“…The Centre for Solar Energy Research (CSER), Swansea University in collaboration with the University of Surrey has developed a thin film cadmium telluride (CdTe) solar cell technology for use in Space . Working with industrial partners Qioptiq Space Technology (QST) and Surrey Satellite Technology Ltd, this solar cell technology is designed to meet the emerging demands of new space applications.…”
Section: Introductionmentioning
confidence: 99%